MINERALOGI GRANITOID BUKIT PAGIAS CEKUNGAN OMBILIN, SUMATERA BARAT - -, Euis Tintin Yuningsih (Bulletin of Scientific Contribution, 2006)
Igneous rocks forming will shows different chemical composition and mineralogy from one phase to another sharply or gradually. This research will study about characteristic of basement rock from Bukit Pagias granitoid complex for detail views. Bukit Pagias granitoid complex have different characteristic although its close each other. Its proved by petrographic analysis that shows different composition of mineralogy. From the color, its shows two kinds of granite i.e. gray granite/monzo-granite (Streckeisen, 1978) and red granite/granite (Streckeisen, 1978), in some part of the area, there are altered red granite and granite wash/weathering granite. The rocks in this area was fractured and filled with silica in part.